2021
DOI: 10.47743/jpd.2021.28.1.878
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Anti-Nutritional Properties of the Seeds of Six Selected Nigerian Cucurbit Germplasm

Abstract: Biochemical characterization of the seed extracts of the seeds of six selected Nigerian cucurbit germplasm was carried out using standard biochemical procedures. All treatments were replicated three times and the results presented as mean ± S.E. On proximate analysis, percentage moisture ranged from (3.83±0.10%) to (5.17±0.65%) with the highest in Lagenaria breviflora (5.17±0.65%) while the least value (3.83±0.10%) was obtained in Cucurbita pepo. Crude protein composition ranged from (32.66-0.11) to (35.94±2.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Percentage ash contents and available energy showed that S. indicum had 5.62±0.76% and 692.22±4.45 k/cal while M. oleifera had 15.13±0.97% and 545.91±3.15 k/cal respectively. Results obtained in the current study is a bit higher than the report of [KARAYE & al. 2021] on three Nigerian cucurbits seeds with the range of values of crude proteins, crude lipids and crude carbohydrates as 32.…”
Section: Proximate Composition Of the Seeds S Indicum And M Oleiferacontrasting
confidence: 90%
“…Percentage ash contents and available energy showed that S. indicum had 5.62±0.76% and 692.22±4.45 k/cal while M. oleifera had 15.13±0.97% and 545.91±3.15 k/cal respectively. Results obtained in the current study is a bit higher than the report of [KARAYE & al. 2021] on three Nigerian cucurbits seeds with the range of values of crude proteins, crude lipids and crude carbohydrates as 32.…”
Section: Proximate Composition Of the Seeds S Indicum And M Oleiferacontrasting
confidence: 90%
“…Hagos et al [97] report an iodine value of 114 g I 2 100 g −1 for cucurbit seed oil. Karaye et al [99] obtained 112.94 g I 2 100 g −1 for Cucurbita pepo and 104.06 g I 2 100 g −1 for Lagenaria breviflora in their study. Yusuf et al [103] and Azam et al [92] report iodine values of 182.74 g I 2 100 g −1 and 121 g I 2 100 g −1 for Cucurbita maxima oil, respectively, while Ibeto et al [98] and Winayanuwattikun et al [100] report 150.37 g I 2 100 g −1 and 95.19 g I 2 100 g −1 for Cucurbita pepo.…”
Section: Quality Of Cucurbits Oil For Biodieselmentioning
confidence: 62%
“…Ikanović et al [86] reported that cold-pressed oil from cucurbit seeds is dark green with a red fluorescence. Karaye et al [99] reported light yellow oil from seeds of Cucurbita pepo and dark brown oil from Lagenaria breviflora. Ibeto et al [98] noted yellow oil from seeds of Cucurbita pepo, dark brown oil from Luffa cyilindrica, and light brown oil from Cucumis melo.…”
Section: Oil Content In Cucurbits Seeds: Potential For Biofuel Produc...mentioning
confidence: 99%
“…Within the vast Cucurbitaceae botanical family, consisting of 125 genera and 960 species, several vegetables stand out for their significance (Karaye et al, 2021;Verdejo-Lucas and Talavera, 2019). Notable species like Cucurbita maxima, C. moschata, C. pepo, C. ficifolia, and C. argyrosperma are widely cultivated (Decker, 1988;Yoo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%